Exploring Student Perceptions on Ai Integration in Academic English Writing Skill Development - Harfiza, Junisa Harfiza; Rachman, Dzul; Rahmawati, Yeni (Borneo Educational Journal (Borju), 2025)
This study explores university students’ perceptions of AI integration in academic English writing using a mixed-methods approach grounded in the Technology Acceptance Model (TAM). Conducted at Universitas Muhammadiyah Kalimantan Timur, it involved 65 questionnaire respondents and five interviewees. Findings revealed that students found AI tools useful for grammar correction, idea generation, and efficiency. However, concerns emerged regarding over-reliance, reduced critical thinking, and limited motivational impact. The study highlights that while AI tools are perceived as beneficial, their adoption lacks affective engagement, especially in contexts with minimal digital literacy training. Originality lies in combining TAM with students’ emotional and contextual experiences in Indonesia, a perspective underrepresented in existing literature. The study recommends structured, reflective pedagogy to support ethical and autonomous AI use in writing.